The role of health insurance on healthcare utilisation among women in Tanzania: insights from Tanzania demographic and health survey 2022 - Amani Anaeli; Alphoncina Kagaigai; Pankras Luoga; Tumaini Nyamhanga; Malale Tungu (Archives of Public Health)
Abstract Background Globally, health insurance is viewed as a viable health financing option for improving access to healthcare. In Tanzania, as in other countries, it is actively promoted to enhance service accessibility. However, there are limited empirical studies on the association between having health insurance and women visiting health facilities. The available studies covered small areas and used small sample size. This study aimed to determine the relationship between health insurance status and utilisation of healthcare among women aged 15–49 using Tanzania Demographic and Health Survey (TDHS). Methodology This study analysed secondary data of 15,254 women drawn from the 2022 (TDHS). The survey is conducted after every five years by the National Bureau of Statistics. The dependent variable was healthcare utilisation status and the key independent variable was health insurance status of a woman. The analysis took into account for complex sampling design. The analysis involved descriptive analysis to get frequency and percentage distribution of respondents. Bivariable analysis and multivariable logistic regression were conducted to assess the magnitude of association between dependent and independent variables. A cut-off point of p-value < 0.05 was used to determine the significant level of statistical significance. Results The prevalence of healthcare utilisation among Tanzanian women was 53%. After controlling for other covariates, women who were covered by health insurance had 1.37 times higher odds of healthcare utilisation compared to those who were not covered by health insurance (AoR:1.37, 95% CI: 1.14, 1.65), women aged 25–34 years had 1.38 times higher odds of healthcare utilisation compared to those who were aged 15–24 years (AoR:1.38, 95% CI: 1.24, 1.54). Women who were in union had 2 times higher odds of healthcare utilisation compared to those who were not in union (AoR: 2.1, 95% CI: 1.88, 2.35). Women who were working had 1.71 times higher odds of utilising healthcare services compared to those who were not working (AoR: 1.71, 95% CI: 1.56, 1.88). Women who watched or listened to mass media at least once a week had 1.37 times higher the odds of healthcare utilisation compared to those who did not watch or listen to mass media at all (AoR:1.37, 95% CI: 1.2, 1.56). However, place of residence was not a significant factor. Conclusion The present study shows a statistically significant association between being insured and the utilisation of healthcare services among women aged 15–49 years. This indicates that insurance status helps women utilise healthcare services in Tanzania. The findings from this study also highlighted demographic factors including age, marital union, working, and use of mass media as important factors influencing utilisation of healthcare among women. It is imperative to educate the community on the importance of health insurance so that more women can enroll in health insurance schemes, including the improved Community Health Fund (iCHF), the National Health Insurance Fund (NHIF), and private health insurance schemes, thereby breaking financial barriers to healthcare utilisation.